LANGUANGE AS A SOURCE OF REJECTION: LOW LITERACY LEARNING AT ORANG RIMBA IN JAMBI PROVINCE - Diana Rozelin; Muhaimin (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Inappropriate use of language in communication makes literacy teaching difficult for Orang Rimba (hereinafter OR). Teachers must have good language skills and appropriate literacy teaching patterns. Based on data, very few teachers are interested in teaching OR groups due to regional, cultural, and natural aspects. The purpose of this research was to know the role of the local language in the delivery of literacy at school. The type of research was qualitative, using descriptive techniques. In collecting data, researchers used observation, interviews, and documentation. Furthermore, the data analysis technique was a descriptive technique that describes the conditions in the field as they are. The respondent who would be interviewed was 1 teacher. The observation area to be studied was Pematang Kabau village at Bukit Dua Belas. The findings were, first, the teacher who teach at school must be able to use OR Malay dialect because Indonesian or Jambi Malay dialect were quite difficult for them to understand. Second, the proper literacy teaching model was the direct learning model implemented for youth and children. Based on the findings above, it can be concluded that choosing the right language and good communication when teaching literacy at OR group must have their own strategy so that what is conveyed can be well received.